Toward Digital Election in Indonesia: Cost Effectiveness Analysis of IVORI (Internet-Voting Republik Indonesia) as an e-Voting System - Purwanti, Desi Ayu; Koerniadi, Teddy (Universitas Gadjah Mada, 2024)
The election in 2019 was held simultaneously, where people directly elected the DPR, DPD, Provincial/ Regency/City DPRD, President and Vice President on April 17, 2019. All the changes in the implementation of elections in Indonesia since 1999, all of them are still carried out using paper. The history of the simultaneous elections in Indonesia in 2019, which were quite expensive, is a consideration for a more sustainable election process. Since the beginning of this century, internet voting has become the most straightforward and prevalent electoral reform adopted by many countries, with the goal of lowering voting expenses by enhancing convenience. This study aims to compare the Cost-Effectiveness Analysis (CEA) of conventional elections using paper ballots with digital-based elections using internet voting (I-voting) and we also developed a prototype of a digital election system called IVORI (I-Voting Republik Indonesia). The results show that elections using the I-voting system are proven to be 71% more cost-effective than conventional systems. IVORI is an internet-based digital election web application that offers two features, namely “VOTING” which will only be active on election day for voters who are eligible to vote and have been previously registered so that they can log in to the application using their ID number and voting station code and the “INFORMASI KANDIDAT” feature which can be accessed by voters during the candidate’s campaign period which contains information about the background and work program plans of each candidate.